Recent advances in risk assessment and risk management of geologic CO2 storage. (September 2015) - Pawar, Rajesh J.; Bromhal, Grant S.; Carey, J. William; Foxall, William; Korre, Anna; Ringrose, Philip S.; Tucker, Owain; Watson, Maxwell N.; White, Joshua A.
Highlights: We provide overview of advances in risk assessment & risk management applications. Four GCS risks defined: containment, performance, public perception, market failure. Understanding of containment & induced seismicity risks has improved. New advances are being made in quantitative and semi-quantitative risk assessment. Risk management approaches have been applied at commercial projects such as Quest. Abstract: This paper gives an overview of the advances made in the field of risk assessment and risk management of geologic CO2 storage (GCS), since the publication of the IPCC Special Report on Carbon Capture and Storage in 2005. Development and operation of a wide range of demonstration projects coupled with development of new regulations for safe injection and storage of CO2 have led to development and deployment of a range of risk assessment approaches. New methods and tools have been developed for quantitative and qualitative risk assessment. These methods have been integrated effectively with monitoring and mitigation techniques and deployed in the field for small-scale field tests as well as large-scale commercial projects. An important development has been improved definition of risks, which can be broadly classed as site performance risks, long-term containment risks, public perception risks and market risks. Considerable experience has now been gained on understanding and managing site performance risks. Targeted research on containment risks and induced seismicity risks has led to improved understanding of parameters and processes influencing these risks as well as identifying key uncertainties that need to be targeted. Finally, significant progress has been made to effectively integrate communication strategies with risk management approaches to increase stakeholder confidence in effectiveness of deployed risk management approaches to manage risks.